DIGITAL DETOX MOTIVATION THROUGH NARRATIVE MEDIA AMONG UNIVERSITY STUDENTS IN MALAYSIA - Mahsal Khan, Syazwani; Ramli, Aida Filzah; Yawadi, Merandee (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
University students’ lives now revolve around social media, but excessive use can lead to anxiety, sleep disturbances, and addictive behaviours. Having digital detoxification as an approach of intentional abstention from social media, therefore, emerged as a self-regulation strategy. Guided by Expectancy–Value Theory (EVT), this study explores how narrative media can influence university students’ motivation for digital detox. EVT offers a pertinent paradigm for comprehending students’ willingness to disconnect from digital platforms by arguing that expectation beliefs, perceived value, and the cost of completing a task determine behavioural intention. Additionally, the Interpretative Phenomenological Analysis (IPA) approach is applied to explore how university students interpret their experiences after watching the narrative short video Unplugged: A Journey Back to Life. Five Malaysian university students aged 18–25 were selected through simple random sampling and participated in semi-structured interviews. Thematic analysis was chosen to identify patterns of meaning across participants’ reflections. The findings showed that three major themes emerged from this study. Firstly, is Emotional Resonance, where participants relate strongly to the protagonist’s feelings of digital overload; secondly, the Visual Symbolism, where colour transitions from cold to warm tones were interpreted as psychological recovery; and finally, the Motivation for Detox, where behavioural intentions varied based on individual expectancy beliefs and perceived benefits. Findings show that while visual cues boost emotional engagement, narrative media can improve digital self-awareness by enhancing perceived value and relatability. According to the study’s findings, university students can benefit from storytelling-based treatments that promote better social media practices and digital well-being.